Studies on preservation of natural dye / Nursharina Mat Dahan - Mat Dahan, Nursharina (Faculty of Applied Sciences, 2009)
This study investigates several methods to preserve dye extract form. Dye content in dried calyses of Hibiscus Sabdariffa was extracted using open Boiling and solvent extraction methods with methanol. A maximum absorbance of crude extract was observed at approximately λmax of 520nm. Natural pigment in liquid crude extract was found unstable and tend to produce a fungi in ambient temperature at only 3 to 4th days of observation. The crude extract from open boiling was freeze dried to form a powderous dyestuff while crude extract from solvent extraction was used to form paste dyestuff. Maltodextrin and lime was added to liquid crude extract as stabilizer and preservatives. The absorbance values were increased which show that the stability of crude extract increased with the addition of preservatives. The results also show that powderous dyestuff with addition of maltodextrin is more stable than paste dyestuff.